Pelatihan Diversifikasi Hasil Perikanan Pada Kelompok Wanita Tani Kelurahan Mamburungan, Tarakan - Kartina; M. Gandri Haryono; Asbar Laga; Dori Rachmawani; Tuty Alawiyah; , Heni Irawati; Yulma; Tiara Hariani Cahyani; Ashariyan; Chritsine Dyta Nugraeni (Literasi: Jurnal Pengabdian Masyarakat dan Inovasi, 2022)
Tarakan has a fairly large potential for fisheries resources, both marine and coastal fisheries (in the form of brackish water / pond aquaculture and freshwater / pond aquaculture). Many Tarakan people work in aquaculture ponds that produce fishery products such as milkfish, crabs, and shrimp. When the harvest arrives, the catch is abundant and fast handling is needed to avoid spoilage. In addition, during the harvest season, the price of fish tends to decrease and is simply sold without considering the selling price. This is due to the lack of public knowledge in terms of fish processing. Whereas with processing into new products, the selling value will increase. Therefore, related training, especially various processed fishery products, is needed to increase public knowledge, especially housewives who are members of women's farmer groups. The method consists of socialization, training and mentoring. The stages of activities carried out in this activity include coordination with women farmer groups, collecting raw materials, outreach to the community, training on fishery products. This training is carried out by processing fish into various products such as pempek and tekwan. The results of the activity show that 90% of women farmers' groups are interested in making various kinds of fish products and women's groups have skills in processing fishery products. Suggestions in this activity are expected to be continued with product packaging and marketing training so that it can provide business opportunities for the Wanita Tani Group, in Mamburungan Tarakan.